The Impact of Caste in the Indian Boardroom - 2024; Purkayastha, Saptarshi (Economic and Political Weekly, 2024)
The opening up of the Indian economy has resulted in breaking caste shackles and creating an educated middle class. Examining the caste affiliations of board members of 89 large Indian companies, it is found that access to modern education, social and political churning that followed the launch of the affirmative actions by the government and the democratisation of availability of capital helped in the creation of a diverse corporate boardroom in Indian companies.
Keywords: Caste Census; Hinduism; Indian Boardroom; Shudra Entrepreneurs; Indian Economy